Concurrent Comparison of the Prognostic Values of Tumor Budding, Tumor Stroma Ratio, Tumor Infiltrating Pattern and Lymphocyte-to-Monocyte Ratio in Colorectal Cancer Patients. (October 2021) - Zhang, Yingcheng; Liu, You; Qiu, Xiaomei; Yan, Bing
Objectives: Tumor budding (TB), tumor stroma ratio (TSR), tumor infiltrating pattern (TIP), and preoperative lymphocyte-to-monocyte ratio (LMR) were previously reported to be useful prognostic factors in colorectal cancer (CRC); however, the correlation among these markers and their individual prognostic potency have not been extensively studied.Methods: A cohort of 147 stage I-IV CRC patients was obtained retrospectively, and the patients were divided into subgroups based on low or high TB/TSR/LMR, TIPa (expansile + intermediate) and TIPb (infiltrative) values. The differences in relapse-free survival (RFS) and overall survival (OS) intervals among these subgroups were determined by Kaplan–Meier analysis followed by log-rank tests. The Cox proportional hazard model was applied for the univariate and multivariate analysis of RFS and OS rates.Results: TB, TIP, and LMR, but not TSR, are useful markers for predicting patient survival. Patients with a poor histological grade and large tumor diameter were more likely to present with high TB, TIPb, and low LMR values; in addition, those with advanced T, N, and TNM stages and elevated preoperative CA199 levels had high TB and TIPb levels. TB, TIP, and LMR were significant prognostic factors for the RFS (TB: HR [hazard ratio] = 2.28, 95% CI = 1.30-4.00, P  < .01; TIP: HR = 2.60, 95% CI = 1.46-4.60, P  < .01; LMR: HR = 0.79, 95% CI = 0.65-0.96, P  = .02) and OS (TB: HR = 2.43, 95% CI = 1.32-4.48, P  < .01; TIP: HR = 2.49, 95% CI = 1.34-4.63, P  < .01; LMR: HR = 0.79, 95% CI = 0.64-0.98, P  = .03) intervals. In addition, TB and LMR were independent prognostic factors for the RFS interval (TB: HR = 1.80, 95% CI = 1.01-3.19, P  = .05; LMR: HR = 0.80, 95% CI = 0.67-0.96, P  = .01), but only LMR was an independent factor for OS rates (HR = 0.80, 95% CI = 0.65-0.98, P  = .03).Conclusion: Although TB, TIP, and LMR are useful prognostic markers for CRC, the LMR is likely to be the only independent prognostic factor for both RFS and OS outcomes in practice.